The Transformation of Judicial Ijtihad in the Indonesian Judiciary in Response to the Escalation of Law: A Maqasid ash-Sharia Perspective - Ahyar Siddiq; Asmuni Asmuni (UIN Sunan Kalijaga Yogyakarta, 2025)
The advancement of human civilization has revealed one of the inherent weaknesses of positive law in fulfilling its function as a framework for social life. Consequently, transformation within the legal system is imperative as a means of enhancing legal certainty within judicial institutions. Judges required to engage in ijtihad (independent reasoning) to facilitate legal transformation and to ensure that the legal order remains responsive and relevant. This study is a literature research study using a qualitative approach. The data used in this study include statutory regulations, books, prior research, and other relevant literatures. The primary objective of this research is to examine how judicial discovery, regarded as a representation of truth in court proceedings, must be interconnected with various supporting instruments to achieve substantive justice in accordance with the framework of Maqasid ash-Sharia. The findings indicate that the incorporation of Maqasid ash-Sharia within judicial ijtihad plays a pivotal role in legal reform aimed at responding to the evolving needs of society. Despite its theoretical significance, the application of this concept in judicial decisions must also be accompanied by the judge’s moral conscience, as both elements collectively guide the judge toward rulings that could realize the public welfare (maslahah). However, this study acknowledges its limitations regarding the practical implementation of its findings. Therefore, future research employing empirical methods within judicial institutions is recommended. Kemajuan peradaban manusia menunjukkan salah satu kelemahan hukum positif dalam memenuhi fungsinya sebagai kerangka kerja bagi kehidupan sosial. Oleh karena itu, transformasi dalam sistem hukum menjadi sangat penting sebagai sarana untuk meningkatkan kepastian hukum dalam lembaga peradilan. Hakim dituntut untuk terlibat dalam ijtihad (penalaran independen) untuk memfasilitasi transformasi hukum dan memastikan bahwa tatanan hukum tetap responsif dan terkini. Penelitian ini merupakan penelitian kepustakaan dengan menggunakan pendekatan kualitatif. Data yang digunakan dalam penelitian ini meliputi peraturan perundang-undangan, buku-buku, penelitian terdahulu, dan literatur lain yang relevan. Tujuan utama dari penelitian ini adalah untuk melihat bagaimana penemuan hukum yang dianggap sebagai representasi kebenaran dalam proses peradilan, harus saling berhubungan dengan berbagai instrumen pendukung untuk mencapai keadilan substantif sesuai dengan kerangka Maqasid al-Syariah. Temuan-temuan ini menunjukkan bahwa penggabungan Maqasid al-Syariah dalam ijtihad yudisial memainkan peran penting dalam reformasi hukum yang bertujuan untuk merespons kebutuhan masyarakat yang terus berkembang. Terlepas dari signifikansi teoretisnya, penerapan konsep ini dalam putusan pengadilan juga harus disertai dengan hati nurani moral hakim, karena kedua elemen tersebut secara kolektif memandu hakim untuk menghasilkan putusan yang mampu mewujudkan kesejahteraan masyarakat (maslahah). Penelitian ini mengakui adanya keterbatasan dalam hal implementasi praktis dari temuan-temuannya. Oleh karena itu, penelitian di masa depan yang menggunakan metode empiris di dalam lembaga peradilan direkomendasikan.